The Rate of Return on Everything, 1870-2015 - Òscar Jordà; Katharina Knoll; Dmitry Kuvshinov; Moritz Schularick; Alan M. Taylor (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper answers fundamental questions that have preoccupied modern economic thought since the 18th century. What is the aggregate real rate of return in the economy? Is it higher than the growth rate of the economy and, if so, by how much? Is there a tendency for returns to fall in the long-run? Which particular assets have the highest long-run returns? We answer these questions on the basis of a new and comprehensive dataset for all major asset classes, including—for the first time—total returns to the largest, but oft ignored, component of household wealth, housing. The annual data on total returns for equity, housing, bonds, and bills cover 16 advanced economies from 1870 to 2015, and our new evidence reveals many new insights and puzzles.
Keywords: D31; E44; E10; G10; G12; N10; 330; return on capital; interest rates; yields; dividends; rents; capital gains; risk premiums; household wealth; housing markets